INTERNALISASI NILAI-NILAI KEAGAMAAN ISLAM PADA JENJANG PENDIDIKAN ANAK USIA DINI - Rusdi Kurnia (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
This study aims to determine the importance of student discipline to the effectiveness of learning in MA Plus Sunan Drajat 7 Silat. Discipline is understood as a rule or order that controls behavior as a form of compliance with norms or rules. Discipline is considered the key to success because it can form a consistent attitude in achieving goals and have a positive impact on the learning process. This study uses a qualitative approach to the type of Field Research (field research). Data collection techniques include interviews, observations, and documentation. The Data obtained were analyzed descriptively to understand the role of student discipline in supporting learning effectiveness. The results showed that student discipline has an important role in improving the effectiveness of learning. Well-applied discipline can create a conducive learning atmosphere, increase student focus, and encourage optimal achievement of learning goals.